Smart Irrigation Controllers: Programming Guidelines for Evapotranspiration-Based Irrigation Controllers - Michael D. Dukes; Mary L. Shedd; Stacia L. Davis (EDIS)
AE445, a 6-page illustrated fact sheet by Michael D. Dukes, Mary L. Shedd, and Stacia L. Davis, is part of the Smart Irrigation Controllers series. It presents programming guidelines for several examples of ET controllers available in Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, February 2009.